Balancing life and work by unbending gender: Early American women psychologists' struggles and contributions. Issue 3 (19th July 2017) - Johnston, Elizabeth; Johnson, Ann
Abstract: Women's participation in the work force shifted markedly throughout the twentieth century, from a low of 21 percent in 1900 to 59 percent in 1998. The influx of women into market work, particularly married women with children, put pressure on the ideology of domesticity: an ideal male worker in the outside market married to a woman taking care of children and home (Williams, 2000). Here, we examine some moments in the early‐to‐mid‐twentieth century when female psychologists contested established norms of life‐work balance premised on domesticity. In the 1920s, Ethel Puffer Howes, one of the first generation of American women psychologists studied by Scarborough and Furumoto (1987), challenged the waste of women's higher education represented by the denial of their interests outside of the confines of domesticity with pioneering applied research on communitarian solutions to life‐work balance. Prominent second‐generation psychologists, such as Leta Hollingworth, Lillian Gilbreth, and Florence Goodenough, sounded notes of dissent in a variety of forums in the interwar period. At mid‐century, the exclusion of women psychologists from war work galvanized more organized efforts to address their status and life‐work balance. Examination of the ensuing uneasy collaboration between psychologist and library scholar Alice Bryan and the influential male gatekeeper E. G. Boring documents gendered disparities in life‐work balance and illuminates how the entrenched ideology of domesticity was sustained. We conclude with Jane Loevinger's mid‐century challenge to domesticity and mother‐blaming through her questioning of Boring's persistent focus on the need for job concentration in professional psychologists and development of a novel research focus on mothering.